Service-Learning and the Construction of a Multicultural Citizenship: The PEINAS Project (Foro de Educacion, 2016)
In a changing context in and for the university, with new organizational approaches coming from the unique situation – such as that associated with the EHEA –, along with the undeniable technological progress; it is also unequivocal the permanence and, at times, the aggravation of social and economic inequalities in the national and international levels. That is why we must try to educate college students through ways and means capable of strengthening a consistent scale of social values and attitudes; taking into account the self-construction of personality and giving special attention to social experiences. Since in a changing social and economic environment, a more conscious and active citizenship, more adaptable and competitive while more supportive and critical, will be the thorough answer. The proposal outlined in this paper considers service-learning as an instruction path inside the classroom, but even beyond the class. Thus, we are presenting the PEINAS project (Multicultural Pedagogy and service-learning), an experience developed at the University of Santiago de Compostela, where students of 2nd year of the Degree in Pedagogy. Within this program, students learn while they are performing a service with organizations working for interculturalism. Among the conclusions reached, most importantly, here and now, it is that service-learning shall be understood as a vector of innovation, with the assistance of other strategies it can produce a better connection between the academic and social dimensions of learning.